2011
DOI: 10.1128/jvi.00316-11
|View full text |Cite
|
Sign up to set email alerts
|

Human Rhinovirus 2 Induces the Autophagic Pathway and Replicates More Efficiently in Autophagic Cells

Abstract: In this study, we tested HRV-2-infected cells for activation of autophagic signaling and changes in virus growth in response to changes in autophagy levels. Our data indicate that HRV-2 induces and subverts the autophagic machinery to promote its own replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 30 publications
5
60
2
Order By: Relevance
“…Tissue culture studies of poliovirus (Jackson et al, 2005), CVB (Wong et al, 2008; Yoon et al, 2008), human rhinoviruses (Brabec-Zaruba et al, 2007; Klein and Jackson, 2011) and enterovirus 71 (Huang et al, 2009) have found only minor changes in virus titer when autophagy is modulated, and there is no clear understanding of precisely which stage(s) of the enterovirus lifecycle are affected. The data in Figure 2 reveal a far greater effect in vivo ; in the absence of intact Atg5, pancreatic CVB3 titers early in infection are reduced by ~3 logs.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue culture studies of poliovirus (Jackson et al, 2005), CVB (Wong et al, 2008; Yoon et al, 2008), human rhinoviruses (Brabec-Zaruba et al, 2007; Klein and Jackson, 2011) and enterovirus 71 (Huang et al, 2009) have found only minor changes in virus titer when autophagy is modulated, and there is no clear understanding of precisely which stage(s) of the enterovirus lifecycle are affected. The data in Figure 2 reveal a far greater effect in vivo ; in the absence of intact Atg5, pancreatic CVB3 titers early in infection are reduced by ~3 logs.…”
Section: Resultsmentioning
confidence: 99%
“…(Jackson et al, 2005) This is true for other picornaviruses, and a large number of viruses, particularly positive-strand RNA viruses, have been shown to benefit from some aspect of the autophagic pathway. (S.-C. Huang et al, 2009; Klein and Jackson, 2011; O'Donnell et al, 2011; Yoon et al, 2008) For poliovirus, the DMVs can act as a substrate for RNA replication, although they play other important roles, discussed below. For Hepatitis C Virus (HCV), autophagy appears be required for initiation of, but not maintenance of, viral replication.…”
Section: Viral Proteins That Trigger the Autophagy Pathwaymentioning
confidence: 99%
“…For example, human Tollip is required for the proper clearance of Huntington's disease-linked polyQ proteins through the ubiquitin-dependent autophagy [19]. As autophagy participates in the anti-RV response in a normal setting [10, 20], Tollip may also serve as a novel mechanism to modulate host responses to RV infection in a type 2 cytokine milieu (e.g., IL-13), a major feature of airway allergic inflammation.…”
Section: Introductionmentioning
confidence: 99%